PENGARUH PARTISIPASI MASYARAKAT DAN TRANSPARANSI PENGELOLAAN DANA DESA TERHADAP KEBERHASILAN PENGELOLAAN DANA DESA DI DESA PERAPAT HILIR KECAMATAN BABUSSALAM - Muhammad Rejeki Gaos; Rila Maufira; Edi Jamaris (Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of community participation and transparency on the success of village fund management in Perapat Hilir Village, Babussalam District, Southeast Aceh Regency. The background of this study is based on the importance of implementing the principles of good governance, especially in the management of village funds, which requires active community involvement and openness of information from the village government. This study uses a quantitative approach with a survey method, where data is collected by distributing questionnaires to respondents who are directly involved in the management and utilization of village funds. The results of the analysis show that transparency has a significant influence on the success of village fund management, while community participation has not made a significant contribution partially. However, simultaneously, both variables play an important role in influencing the level of success of village fund management. This finding confirms that openness of information carried out consistently and systematically by the village government is a key factor in encouraging accountability and effectiveness in the use of village funds. This study has implications for strengthening more transparent and participatory village governance policies. In addition, this study is also expected to be a reference for further research in examining other variables that also influence the effectiveness of village fund management in various regional contexts